(untitled) (Studies in Comparative Education, 2023)
The article presents the results of the teachers’ survey conducted as a part of the OAEE project ("Organization of the Accessible Educational Environment for Internally Displaced Persons under the Martial Law in Ukraine") with the support of the Ukrainian Educational Research Organization (UERA) and the European Educational Research Organization (EERA). The questions of the survey concerned the issue of an accessible educational environment for children of the internally displaced people in the context of interaction and teaching in general secondary education institutions of Ukraine. The purpose of the research was to summarize the diverse experience, understanding and opinions of teachers on the organization of the educational process under the martial law in Ukraine. The teachers were asked about the education format in their schools, the e-learning platforms they mostly used, the forms of communication with students and parents they preferred, the strategies of teaching and the ways of integration of children and their families into the new living and learning environments, in order to collect and analyse the information about the teaching process over the past year of war in Ukraine. The analysis of teachers’ opinions on the problem of an accessible, comfortable, safe educational environment has made it possible to identify some issues that need further discussion and development: the teachers’ need for the methodological support of the courses on topics relevant to the crises situations, the lack of knowledge on the effective forms and methods of psychological support for children and parents who are forced to change their places of residence due to military aggression; the needs for the recommendations on how to provide the accessible, safe educational environment with the effective feedback and objective assessment of students’ academic achievements. The results of the study are presented in the form of recommendations which help ensure quality education for the children of internally displaced people and take their special circumstances into account.